Cash flow ratios as a yardstick for evaluating financial performance in Malaysian businesses / Junizza Imieyantie Ibrahim - Ibrahim, Junizza Imieyantie (2007)
This study is to evaluate the financial performance in Malaysian businesses. For this purpose, Malaysian companies will be compared with US companies in the consumer product, industrial product and trading products. The cash flow ratios will be using in order to evaluate the financial performance of the companies. There will be 5 companies from each sector. Ratios will be calculated from year 2001 until 2005. The performance of companies in term of profit will be the dependent variable while the cash flow ratios will be the independent variables. Regression analysis will be using as a method for this study. From this study, it will shows that the cash flow ratios as a yardstick for evaluating the Malaysian companies performance as compared to US companies and will revealed some similarities and differences. From the result it shows that there is relationship between cash flow ratios and the performance of both countries. It revealed similarities among the countries. On the other side, it shows that the value of R2 for US companies is lesser than value of R2 for Malaysian companies. US companies have negative relationship between the sufficiency ratio and the profitability of the company while Malaysian companies have a positive relationship between the sufficiency ratio and the profitability of the companies. It was tested in the multiple regressions and shows the same negative relationship.